The relationship between commodity price volatility and exchange rate stability in a single commodity dependent economy: The case of Zambia - Anderson, Larry (Research of GSB, 2017)
This study examines the empirical relationship between monthly spot copper price movements and monthly Zambian Kwacha / US Dollar spot exchange rates, for the period January 2005 to February 2015. The ARDL bounds short-run estimate reveals there is both positive and negative coefficient interaction of copper price movements on the exchange rates in the short-run. However, the overall impact of copper prices on the exchange rate, is not significant in the short-run. The ARDL bounds test also confirms the presence of a long-run relationship between copper prices and the exchange rate. The coefficient estimates reveal that both the consumer price index and the terms-of-trade have a statistical weak impact on the exchange rate in both the short and long run. The study finds that Zambia's GDP has a negative impact on the exchange rate in the short-run, but has a statistically significant positive long-run effect. China's GDP, is used as a proxy to capture foreign demand for copper, it has both a positive and negative interaction on the exchange rate in the short-run and a negative effect in the long-run.